2022
DOI: 10.1021/acs.langmuir.2c01098
|View full text |Cite
|
Sign up to set email alerts
|

HF Resistant Porous Aromatic Frameworks for Electronic Special Gases Separation

Abstract: Here we report two HF acid resistant porous aromatic frameworks as adsorbents for high value-added electronic special gases (e.g., SF 6 , NF 3 , CF 4 , Xe, Kr) separation. The New-PAF-1 and N-SO 3 H exhibit exceptional adsorption selectivity for Xe and F-gases from semiconductor exhaust gas along with high physicochemical stability and excellent reusability, which have been collaboratively confirmed by single-component gas adsorption experiments, time-dependent adsorption rate tests, dynamic breakthrough exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This is because NH 2 − Ni-MOF possesses a smaller ultra-micropore and stronger affinity to CF 4 molecules, thus leading to higher selectivity. To the best of our knowledge, this selectivity of CF 4 /N 2 (1/9) in NH 2 −Ni-MOF is the highest in all reported porous materials for CF 4 /N 2 separation (Figure 4e and Table S2), such as PAF-4F (4.68), 37 F-cage (4.04), 38 New-PAF-1 (∼5), 39 and Cu(peba) 2 (2.25), 40 notably higher than that of the benchmark C-PVDC-600 (18.6). 25 Ni-MOF and NH 2 −Ni-MOF eliminate the tradeoff between the separation selectivity and adsorption capacity (Figure 4e).…”
Section: Resultsmentioning
confidence: 83%
“…This is because NH 2 − Ni-MOF possesses a smaller ultra-micropore and stronger affinity to CF 4 molecules, thus leading to higher selectivity. To the best of our knowledge, this selectivity of CF 4 /N 2 (1/9) in NH 2 −Ni-MOF is the highest in all reported porous materials for CF 4 /N 2 separation (Figure 4e and Table S2), such as PAF-4F (4.68), 37 F-cage (4.04), 38 New-PAF-1 (∼5), 39 and Cu(peba) 2 (2.25), 40 notably higher than that of the benchmark C-PVDC-600 (18.6). 25 Ni-MOF and NH 2 −Ni-MOF eliminate the tradeoff between the separation selectivity and adsorption capacity (Figure 4e).…”
Section: Resultsmentioning
confidence: 83%
“…For example, recent studies showed that the deployment of high-density aromatic rings into a framework is beneficial to form multiple FÁ Á Áp interactions with fluorinated-gases, although SF 6 is prone to form a strong interaction with the polar groups. 308 An ultramicroporous Nibased MOF material (Ni(NDC)(TED) 0.5 ) (H 2 NDC = 1,4naphthalenedicarboxylic acid, TED = triethylenediamine) with a pore surface featuring naphthalene rings shows excellent separation performance of SF 6 /N 2 . 295 To the best of our knowledge, Ni(NDC)(TED) 0.5 has the highest SF 6 adsorption capacity (2.8 mmol g À1 ) under a pressure of 0.1 bar which corresponds to the partial pressure of SF 6 in a practical mixture.…”
Section: Perfluorinated Gas/n 2 Separation Using Apm Adsorbentsmentioning
confidence: 99%
“…Wherein, Mn 3 (HCOO) 6 with the largest pore size exhibited best SF 6 /N 2 selectivity of 263 (SF 6 : N 2 = 9 : 1), and Ni 3 (HCOO) 6 with smallest pore is more suitable for the capture of smaller CF 4 and NF 3 with high CF 4 /N 2 and NF 3 /N 2 selectivity. 308 Recently, Zhang et al fabricated a polypyrene porous organic framework (termed as Ppy-POF) with excellent acid resistance for electron specialty gas adsorption. The GCMC simulations demonstrated the overlap between the van der Waals surface of perfluorinated gases with negative potential and hydrogen atoms from polypyrene in Ppy-POF with positive potential, indicating the FÁ Á ÁH interactions.…”
Section: Perfluorinated Gas/n 2 Separation Using Apm Adsorbentsmentioning
confidence: 99%
“…18−23 However, in recent years, the emission of SF 6 has increased sharply with the rapid development of the semiconductor industry and the construction of power systems. 24,25 To control the emission of SF 6 and reduce its impact on the environment, the proposed approach involves filling the primary absorption vessel with adsorbent filter beds and employing the pressure swing adsorption method. By applying pressure to the primary absorption vessel, efficient separation and collection of SF 6 gas can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of gas adsorption, the adsorption of SF 6 is an important research topic. This is mainly because SF 6 , a typical fluorinated gas, has been widely used in various applications in the distribution industry as an electrical insulation gas and etchant in semiconductor production, owing to its excellent insulating and inert stability properties. However, in recent years, the emission of SF 6 has increased sharply with the rapid development of the semiconductor industry and the construction of power systems. , To control the emission of SF 6 and reduce its impact on the environment, the proposed approach involves filling the primary absorption vessel with adsorbent filter beds and employing the pressure swing adsorption method. By applying pressure to the primary absorption vessel, efficient separation and collection of SF 6 gas can be achieved.…”
Section: Introductionmentioning
confidence: 99%